ISOLATION OF CELLULOSE DEGRADING FUNGI FROM SOIL AND OPTIMIZATION FOR CELLULASE PRODUCTION USING CARBOXY METHYL CELLULOSE: Life Sciences-Microbiology - PRIYANKA P; YUVRAJ C; FARHA S; ARANGANATHAN V (International Journal of Life Science and Pharma Research, 2022)
Cellulose is a linear polysaccharide composed up of glucose residues. Cellulose can be broken down by microorganisms which mainly utilize sugars for their growth. The main objective of the present study was to isolate a potential fungal strain and to optimize the culture conditions to get maximum cellulase. Potential fungus was isolated, screened and identified for cellulase production and the culture conditions were optimized. Study revealed the best condition for cellulase production for fungi was found to be pH 6 with temperature 30°C±2 and ammonium chloride as nitrogen source supported the maximum cellulase production of 0.117U/ml.